Comparative statistical study of characteristics of plasma in planar and non-planar ICME sheaths during solar cycles 23 and 24 - Shaikh, Zubair I.; Raghav, Anil N.; Vichare, Geeta; Bhaskar, Ankush; Mishra, Wageesh (My University, 2020)
Planar magnetic structures (PMS) are often observed in sheath regions driven by interplanetary coronal mass ejections (ICMEs) and in corotating interaction regions (CIRs). Here, we study plasma properties statistically within planar and non-planar ICME sheath regions using in situ data from the Advanced Composition Explore (ACE) spacecraft. The study includes 420 ICME driven sheaths from 1998–2017. We found that 146 (∼ 35 per cent) ICME-driven sheaths are planar, whereas 274 (∼ 65 per cent) are non-planar. This study found that the average plasma temperature, density, speed, plasma beta, thermal pressure and magnetic pressure are higher in planar sheaths than in non-planar sheaths. This implies that high compression plays an essential role in the formation of PMS in sheath regions. Interestingly, our analysis reveals explicitly that the strength of the southward/northward magnetic field component is almost double in planar sheath regions compared with non-planar sheath regions. This suggests that planar sheaths are more geoeffective than non-planar sheaths.
Keywords: MHD; turbulence; Coronal Mass Ejections; CMEs; Solar wind; Interplanetary coronal mass ejections